2018
DOI: 10.1126/sciadv.aau4914
|View full text |Cite
|
Sign up to set email alerts
|

Impact of modular organization on dynamical richness in cortical networks

Abstract: Balance of functional integrability and spatial segregation mediates dynamical richness in modular cortical networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
129
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(134 citation statements)
references
References 42 publications
(83 reference statements)
5
129
0
Order By: Relevance
“…In the context of highly modular architectures, this long range loss turns into a favorable mechanism that allows the maintenance of activity in localized regions. We also note that, if damage is viewed as a controlled silencing of neurons, spatial features provide direct mechanisms to dynamically couple microcircuits, allowing to tune the dynamical state of the system from whole-network activation to segregated activity, in the same fashion as observed in the functional organization of engineered neuronal cultures 35 and brain networks. 36,37 In a nutshell, our work sheds light on two central results.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the context of highly modular architectures, this long range loss turns into a favorable mechanism that allows the maintenance of activity in localized regions. We also note that, if damage is viewed as a controlled silencing of neurons, spatial features provide direct mechanisms to dynamically couple microcircuits, allowing to tune the dynamical state of the system from whole-network activation to segregated activity, in the same fashion as observed in the functional organization of engineered neuronal cultures 35 and brain networks. 36,37 In a nutshell, our work sheds light on two central results.…”
Section: Discussionmentioning
confidence: 89%
“…An important strength of our work is that it lays the foundation for mimicking the structure of living circuits, in particular, neuronal cultures, and study their behavior upon damage. Recent studies 35 have shown the potential of neuroengineering to prepare speci c con gurations such as modular circuits. Thus, we can use our approach to predict the vulnerability of certain designs and explore possible recovery mechanisms of the living networks.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments in combination with network analyses thus provide an excellent platform to relate connectivity failure with functional alterations and recovery mechanisms. The gap between in vivo and in vitro architectures can be reduced through neuroengineering, which allows to mimic major organizational (Aebersold et al, 2016) and dynamical (Yamamoto et al, 2018) features of brain circuits while maintaining full access to neurons and connections. The analysis of damage and recovery in these advanced designs will open new avenues for understanding the link between complex network topologies, damage and functional resilience, more prominently in the context of modular organization (Sporns and Betzel, 2016), and node centrality (Alstott et al, 2009;Fornito et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…According to previous reports, in vitro systems constitute a successful experimental model of neuronal dynamics ( 30, 31 ), thus providing an excellent test bed for adaptive closed-loop neural interfaces ( 32 ). Starting from our recently developed methodology ( 33 ), we created custom bimodular cultures with the goal of reproducing two interacting neuronal populations, thus mimicking the intrinsic modularity of the brain ( 17, 34 ). Our bimodular cultures were highly temporally stable in terms of firing properties at the whole network level as the activity between the two populations remained highly correlated for the entire duration of the recording.…”
Section: Discussionmentioning
confidence: 99%